Presymptomatic diagnosis of von Hippel-Lindau disease with flanking DNA markers. Issue 12 (December 1992) - Maher, E R; Bentley, E; Payne, S J; Latif, F; Richards, F M; Chiano, M; Hosoe, S; Yates, J R; Linehan, M; Barton, D E
Abstract : Von Hippel-Lindau (VHL) disease is a dominantly inherited cancer syndrome characterised by the development of retinal, cerebellar, and spinal haemangioblastomas, renal cell carcinoma, and phaeochromocytoma. The gene for VHL disease has been mapped to chromosome 3p25-p26 and flanking markers identified. We have investigated the usefulness of currently available DNA markers for the presymptomatic diagnosis of VHL disease. In the first part of this investigation, genetic linkage data from two previously published studies were updated and reanalysed to provide accurate estimates of sex specific recombination fractions and to confirm that there is no evidence of locus heterogeneity. In the second part of this study, 14 families containing 23 asymptomatic subjects at 50% prior risk of VHL disease were investigated with closely linked DNA markers (RAF1, D3S18, D3S732). Seventeen subjects were informative with one or more markers, six of whom were informative at markers flanking the VHL disease gene. By combining age related and DNA based risk information the carrier risk for 11 subjects was reduced to < 2%.